Teacher performance at SMAN 24 Bandung: analysis of work environment, discipline and ability - Mutiara Nova Ayu; Lili Kania (Institute of Computer Science (IOCS), 2023)
This research aims to analyze teacher performance at SMAN 24 Bandung with a focus on factors that influence performance, namely work environment, discipline and ability. Teacher performance is an important element in the education system, and a deep understanding of the factors that influence teacher performance is very necessary to improve the quality of education. The research results show that the simultaneous influence of the work environment, discipline, and ability on teacher performance is positive. However, the influence of each of these factors tends to be small scale. The results of this research show the importance of paying attention to discipline and developing teacher abilities in improving teacher performance, even though the work environment has a negative influence, it is still a concern for schools because it supports the teaching and learning process.